Fine-tuned order-order phase transitions in giant surfactants via interfacial engineering. (March 2020) - Shan, Wenpeng; Zhang, Wei; Huang, Mingjun; Ji, Yuyang; Zhang, Ruimeng; Zhang, Rui; Su, Zebin; Liu, Hao; Feng, Xueyan; Guo, Dong; Huang, Jiahao; Liu, Tong; et al.
Highlights: Order-order phase transitions (OOTs) controlled via different rigid junction segments. Four different ordered phases appeared in one sample by changing temperature. Simple two-state model proposed to expound the mechanisms of OOTs. Abstract: Thermotropic order-order phase transitions (OOTs) in block copolymers are not commonly observed in the strong segregation region. Phase separation of giant surfactants composed of hydrophilic molecular nanoparticles (MNPs) as heads and hydrophobic flexible polymer chains as tails occurs generally in the strong segregation region. By introducing a rigid molecular segment at the junction point of the giant surfactants, the interface between the MNPs and polymer tails could be delicately manipulated, resulting in the occurrence of thermotropic OOTs that are sensitively dependent on the properties of those junction segments. For samples with hydrophilic junction segments, no thermal-induced OOT has been observed. However, for samples with hydrophobic junction segments, complicated thermotropic OOTs between as many as four different ordered phases in a single giant surfactant system, from lamellae (LAM) to hexagonally perforated layer structure (HPL), double gyroids (DG), and finally to hexagonally packed cylinders (HEX), have been observed with increasing temperature. These results demonstrated that interfacial engineering could be used to regulate the self-assemble behavior of macromolecules at the nanometer scales. Graphical abstract: Image, graphical abstract